Enhancing Non-Vocational Teacher Professional Development through an Andragogical Internship Model - Siti Maspupah; Jajat Sudrajat Ardiwinata; Yanti Shantini (AL-ISHLAH: Jurnal Pendidikan, 2025)
This study aims to develop an internship model based on andragogical principles to enhance the skills and competencies of non-vocational teachers. Andragogy focuses on adult learners' needs, leveraging their prior knowledge and experiences as the foundation for learning. The research follows a Research and Development (RD) approach, incorporating needs analysis, model design, development of teaching materials, and field trials. Non-vocational teachers from various schools and regions participated in the trials. Data were collected via observations, interviews, and questionnaires to assess the model's effectiveness and relevance. The findings show that the andragogical internship model provides a relevant and applicable learning experience for non-vocational teachers. It enhances both practical teaching skills and theoretical knowledge that can be applied directly in the classroom. This model offers a contextual and experience-based approach to teacher development, potentially improving the professionalism of non-vocational teachers. It presents an effective alternative to traditional teacher training, enhancing the quality of teaching and learning across different educational levels.